STUDY OF FORTIFIED BISCUIT QUALITY WITH CATFISH’S (Pangasius sp) SWIM BLADDER FLUOR - Joshbusst hamido; Dewita Dewita; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This study aims to assess the quality of biscuits fortified with catfish swim bladder flour and to determine the amount of fish swim bladder flour with the best quality biscuits. The research method was carried out experimentally with the fortification of different fish swim bladder flour, with a completely randomized design (CRD) consisting of four treatment levels, namely: without the addition of fish swim bladder flour (To), addition of 5% fish swim bladder flour. (T1). , 10% (T2), and 10% (T3).Analysis of the parameters of the organoleptic biscuits, moisture, ash, protein, fat, and carbohydrate content. The results showed that the addition of catfish swim bladder flour affected the quality of the biscuits. The swim bladder flour 5% (T1) was the best treatment to produce the quality biscuits characteristics which had a pale yellow biscuit color, a distinctive biscuit aroma, a combination of sweet and savory flavors, and a crunchy texture; the moisture content of 5.95%, ash 1.01%, 23.54% fat, 6.30% protein, and 63.42% carbohydrates. Keywords: biscuits, swim bladder, Pangasius sp